2018
DOI: 10.13189/ujer.2018.060918
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Three-level Framework for Building Information Modeling Education in Construction Management

Abstract: As Building Information Modeling (BIM) became the gold standard of the architecture, construction, and engineering industry, lack of skilled BIM professionals is considered one of the major challenges. While numerous studies have identified different approaches to introduce BIM in construction management (CM) programs, comprehensive frameworks have not been found. To bridge the gap, this paper proposes a three-level framework that provides a systematic coverage of BIM through the entire CM curriculum. The fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Establish a construction period assurance system organized by the project manager and participated by different professional leaders to clarify the completion of objectives in different flow sections, analyze the interference factors that may affect the construction period, give human intervention and positive feedback when necessary, and optimize the construction scheme appropriately according to the possible change factors to ensure the orderly completion of various projects. The progress plan shall be formulated hierarchically, and the construction and production shall be organized according to the project progress [12]. The project planner shall customize a scientific monthly production plan based on the overall construction progress of the project.…”
Section: Time Control Measuresmentioning
confidence: 99%
“…Establish a construction period assurance system organized by the project manager and participated by different professional leaders to clarify the completion of objectives in different flow sections, analyze the interference factors that may affect the construction period, give human intervention and positive feedback when necessary, and optimize the construction scheme appropriately according to the possible change factors to ensure the orderly completion of various projects. The progress plan shall be formulated hierarchically, and the construction and production shall be organized according to the project progress [12]. The project planner shall customize a scientific monthly production plan based on the overall construction progress of the project.…”
Section: Time Control Measuresmentioning
confidence: 99%
“…Similarly, Hu et al (2018) demonstrated how BIM enabled pedagogy (BEP) has a more effective approach than traditional teaching methods. The quest for BIM-enabled education has led to many scholars investigating approaches to integration of BIM in education (Sampaio, 2018;Garyaeva, 2018;Huang, 2018;Ferrandiz et al, 2018).…”
Section: Building Information Modelling and Health And Safetymentioning
confidence: 99%